Hakikat Manusia dalam Tasawuf Al-Ghazali - Asmaya, Enung (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
Sufism is one of the Islamic sciences that specifically addressed the inner truth of a man (hakikat). Human existence is very dependent on the inner side, from this, human could be directed into a positive (taqwa) or negative person (fujur). Moreover, study of this hakikat is usually done through a sufistic approach. Some of the well-known Sufi figures whose worthy of research is Abu Hamid Muhammad al-Ghazali ath-Thusi asy-Shafi’I, commonly called Imam al-Ghazali. The study of the hakikat conducted by Ghazali is very influential on the Islamic world and in fact modern-west. This study uses library research approach using books and literatures on his thoughts especially related to the subject of a man and Sufism. Result from this study shows that according to Ghazali, the concept of hakikat or the inner truth is posits inside an integrated individual soul and body, the soul as determinant of life and body as a container of the soul. If someone’s soul is clean (taqwa) then the body is also become clean (taqwa) and vice versa if his soul is dirty (fujur) then the body is become negative (fujur). Hakikat would be appeared when a man become a ma’rifatullah . The attainment of the soul into ma’rifatullah stage must go through three processes. firstly takhalli , secondly, tahalli and tajalli and the third is al-nafs almuthma’innah which means having a calm and peaceful soul to be always together with the eternal substance.